PROPOSED IMPROVEMENT OF DIGITAL BILL PAYMENT SOLUTION (CASE STUDY AT PT AYOPOP TEKNOLOGI INDONESIA) - Mallika Nandini, Bina
Ayoconnect is a fintech company that develops bill payment APIs. In order to improve their business’ value proposition, Ayoconnect needs to understand the external and internal business environment and identify the challenges and opportunities that relate to digital bill payment services in Indonesia. This study used a combination of quantitative methods using a survey that is based on the SERVQUAL framework and Importance-Performance Analysis (IPA) matrix to analyse customers’ satisfaction level, as well as a qualitative approach through direct observation and information gathering using using the SWOT framework and the PESTLE framework to build strategy recommendations. The respondents for this survey are 170 Indonesian customers aged 16 to 45 years old who are living in middle class households and have paid their bills through any digital platforms at least once between January and March 2021. The survey results were then mapped into the Importance Performance Analysis matrix. The study found that digital platforms that provide bill payment solutions have generally met or exceeded their customers’ expectations on tangibility, responsiveness, and empathy dimensions, but failed to meet their expectations on reliability and assurance dimensions. Based on their positions in the Importance-Performance Analysis (IPA) matrix, service attributes under the responsiveness dimension and empathy dimension are categorized under the Low Priority quadrant. Service attributes under the tangibility dimension, reliability dimension, and assurance dimension fall under the Keep Up the Good Work quadrant.